Assessing the Prebiotic Potential of Taro (Colocasia esculenta) with Probiotic Lactobacillus Species in an in Vitro Human Digestion System (P20-022-19). (13th June 2019) - Saxby, Solange; Li, Yong; Lee, Chin; Kim, Yong Soo
Abstract: Objectives: Taro ( Colocasia escuknta ), a culturally important staple food of the native Hawaiian diet, is high in fiber content, reaching 4.1 g/100 g. Prebiotics are carbohydrates that are indigestible by the digestive tract, which can selectively stimulate probiotic growth and/or activities in the colon. Due to taro's high fiber content, it was hypothesized to have prebiotic potential. This study aimed to evaluate the effect of taro on the growth and adherence of probiotic Lactobacillus species in an in vitro human digestion system for the improvement of the human gut microbiome. Methods: Four probiotic Lactobacillus species, including L. acidophilus, L. paracasei, L. rhamnosus, and L. plantarum, were individually paired with 2% (w/v) taro. In addition to taro, 2% (w/v) glucose and inulin were used as controls. The pairings were subjected to an in vitro human digestive tract simulation of the mouth, stomach, and intestinal conditions to assess the fate of tested probiotics. Furthermore, an auto-agglutination assay was conducted to evaluate the effect of taro on self-agglutination of the individual probiotics. Lastly, the Caco-2 cell line was used to determine whether taro could influence the ability of tested probiotics to adhere to human intestinal epithelial cells. Results: Results indicated that L. acidophilus, L. paracasei, and L. plantarum experienced greater growth in the simulated intestinal tract when paired with taro than with inulin or glucose. In addition, L. paracasei showed strong self-agglutination ability and had the greatest adherence percentage to Caco-2 cells. Conclusions: In conclusion, taro is a strain-specific potential prebiotic that can be utilized as a dietary aid to modulate a healthy gut microbiota. Funding Sources: USDA-ARS. USDA-NIFA Hatch University of Hawai'i Mānoa MahiMicrobes Program